Zidovudine-induced pigmentation on skin, nail and oral cavity – a study on 119 patients - Shoubin, Mohammed; Kandasamy, Muthusamy; Gopalan, Kannan; vellaisamy, Seethalakshmi Ganga; Manickam, Navakumar (Journal of Pakistan Association of Dermatologists, 2018)
Objective To assess the incidence of zidovudine induced pigmentation among HIV-infected patients. Methods All HIV patients who were receiving antiretroviral therapy (ART) with mucocutaneous pigmentation were screened and those receiving zidovudine were included in the study. Proper mucocutaneous examination was done. Site, duration of lesions and duration of treatment were taken into consideration. All the collected data were recorded and statistically analyzed. Results A total of 119 HIV infected patients on zidovudine were included in the study. Majority of the study population (52.9%) was on ART for more than 5 years. 114 patients were on zidovudine, lamivudine and nevirapine regimen and 5 patients were on zidovudine, lamivudine and efavirenz regimen. Pigmentation over nails was seen in 33 patients and 31 patients had both nail and oral mucosal pigmentation. Skin, nail and oral cavity pigmentation was there in 24 patients. For majority, i.e. 63 patients, nail was the first site to be involved. Conclusion Hyperpigmentation is a major side effect with prolonged treatment of zidovudine. Prior explanation regarding adverse reactions may improve outcome of the therapy, as well as, adherence to the antiviral drug regimen.